Percepções de médicos intensivistas brasileiros sobre o uso do ecocardiograma à beira-leito - Fonseca, Simone de Medeiros (2022)
Simone MF. Perception of Brazilian Intensive Care Physicians about the use of bedside Echocardiogram. The use of bedside echocardiogram by intensive care physicians has become a valuable tool to make up the evaluation, assertive diagnosis, management of hemodynamic status, risk stratification and therapeutic interventions of adult critical lye patients hospitalized in intensive care units. The study aimed to elaborate and validate an instrument to characterize the profile of professional training of Brazilian intensive care physicians regarding the use of echocardiogram at the bedside and to identify the perception of intensive care physicians who performed training in the use of bedside echocardiogram on competencies for its use and improvement of care with the use of this tool. This is observational, transverse, descriptive research of quantitative approach. Ninety physicians associated with the Brazilian Association of Intensive Care Medicine participated. Participants answered a self-administered online questionnaire, validated by six judges, which covered three domains: training for bedside echocardiogram; use of bedside echocardiogram; characterization of participants. The results were organized in tables and analyzed according to the absolute and relative frequency of their variables. It was found that 64% of the participants were trained to use the bedside echocardiogram, mostly in continuing medical education courses, with a workload of more than 12 hours; 84% reported being able to perform the exam without the help of another professional after training; 72% were able to discuss the results obtained with more experienced professionals; 79 to 93% of the respondents affirmed the development of specific skills after training of the tool. On the other hand, 55% of the sample considers itself little or almost nothing capable of using this resource in their practice. Both the perception of skills acquired after training, as well the type of training and the total workload of the course did not influence the participants' abilities to perform the evaluation of basic measures to answer objective and targeted clinical questions, as recommended by the literature